Pre- and syn-eruptive dynamics of coexisting andesite and basaltic-andesitic magmas driving the November 2024 eruption of Lewotobi Laki-laki, Indonesia - Gabriela Nogo Retnaningtyas Bunga Naen; Muhammad Andriansyah Gurusinga; Indranova Suhendro; Andrea Agangi; Manuel Nopeia; Geri Agroli; Dini Nurfiani; Wilfridus Ferdinando Supriyadi Banggur; Andhika Nugraha (Journal of Volcanology and Geothermal Research, 2026)

Flood-driven nutrient influx and phytoplankton succession in the subtropical waters of the Matsu Archipelago, Taiwan - Supriyadi; Yun-Chi Lin; Wan-Lin Chen; Kuo-Shu Chen; Gwo-Ching Gong; Sheng-Fang Tsai (Continental Shelf Research, 2026)

An explainable data-driven framework for short-term residential energy forecasting - Julien Nkunduwera Mupenzi; Deden Witarsyah; Adhi Kusnadi; Aswan Supriyadi Sunge (Energy and Buildings, 2026)

Thermal pretreatment-induced modulation of pungency-related compounds and flavor via free amino acids in Lokio (Allium chinense G. Don) - Eva Mayasari; Supriyadi Supriyadi; Retno Indrati; Widiastuti Setyaningsih (Food Research International, 2026)

Tyrosinase-mediated oxidation for the valorization of immature Robusta coffee: Sensory and chemical impacts - Vita Fitriani; Andriati Ningrum; Widiastuti Setyaningsih; Supriyadi Supriyadi (Biocatalysis and Agricultural Biotechnology, 2026)

Evaluation of the potential of replanted rubber wood and palm oil waste with coal as co-combustion fuels in a lab-scale combustion simulator: ash deposition aspects - Hariana Hariana; Adi Prismantoko; Suyatno Suyatno; Hafizh Ghazidin; Fairuz Milkiy Kuswa; Ade Sana Ruhiyat; Cuk Supriyadi Ali Nandar; Muhamad Iqbal Felani; Widi Pancono; Unggul Priyanto; Kusmiyati Kusmiyati; Hari B. Vuthaluru (Biomass and Bioenergy, 2025)

Volatile compounds and aroma descriptions in overfermented tempe (tempe bosok) with different packaging and blanching treatment - Tata Trapsila Larasati Pamekas; Dwi Larasatie Nur Fibri; Supriyadi Supriyadi (International Journal of Gastronomy and Food Science, 2025)

Monetary value of ecosystem services in unhealthy seagrass meadows in Indonesia - Nurul Dhewani Mirah Sjafrie; Puji Rahmadi; Triyono Triyono; Fery Kurniawan; Indarto Happy Supriyadi; Firman Zulpikar; Luky Adrianto; Susi Rahmawati; Udhi Eko Hernawan (Ecosystem Services, 2024)

Analysis of radiative heat flux using ASTER thermal images: Climatological and volcanological factors on Java Island, Indonesia - Dini Andriani; Supriyadi; Muhammad Aufaristama; Asep Saepuloh; Alamta Singarimbun; Wahyu Srigutomo (Remote Sensing Applications: Society and Environment, 2024)

Metagenomic profiling of rhizosphere microbiota: Unraveling the plant-soil dynamics - Atif Khurshid Wani; Farida Rahayu; Abdullah M. Alkahtani; Maha Awjan Alreshidi; Krishna Kumar Yadav; Parnidi; Lilia Fauziah; Mala Murianingrum; Nahid Akhtar; Elya Mufidah; Supriyadi; Dyah Muji Rahayu; et al. (Physiological and Molecular Plant Pathology, 2024)

Robust inversion of 1D magnetotelluric data using the Huber loss function - Elfitra Desifatma; I. Gede Putu Fadjar Soerya Djaja; Prihandhanu Mukti Pratomo; Supriyadi; Enjang Jaenal Mustopa; Maria Evita; Mitra Djamal; Wahyu Srigutomo (Computational Geosciences, 2024)
In this study, a robust 1D inversion was performed on magnetotelluric (MT) data by utilizing the Huber loss function to avoid misleading interpretation of results, which is caused by the presence of outliers in the data. The MT method utilizes the ratio between the electric field (E) and the magnetic field (H), which are perpendicular to each other, to obtain impedance values (Z). These values are used to extract subsurface information in the form of electrical resistivity variations with depth. In the study, forward modeling of the 1D MT responses was conducted by recursively calculating Z values. Robust inversion was performed using the Huber loss function as an objective function to minimize the difference between the calculated and observed data. The Huber loss function combines the squared loss and the absolute loss to anticipate the presence of outliers in MT observation data. The robust inversion was performed on synthetic data with additional noise and field data. The inversion process utilized 50 layers with a thickness of 500 m, a hyperparameter $$\varvec{δ }= 5× {10}^{-2}$$ δ = 5 × 10 - 2 , $$λ =0.01$$ λ = 0.01 , and $${λ }_{t}=100$$ λ t = 100 . The number of iterations used was 500 for inversions that used synthetic data and 3000 for inversions that used field data. The robust inversion scheme using the Huber loss function successfully overcame the presence of outliers and accurately estimated the actual model parameters, both for synthetic data and field data that contained outliers. The misfit was relatively small and close to zero, indicating that the inversion code works well.

Environmental resilience through artificial intelligence: innovations in monitoring and management - Atif Khurshid Wani; Farida Rahayu; Ilham Ben Amor; Munleef Quadir; Mala Murianingrum; Parnidi Parnidi; Anjuman Ayub; Supriyadi Supriyadi; Sakiroh Sakiroh; Saefudin Saefudin; Abhinav Kumar; Evy Latifah (Environmental Science and Pollution Research, 2024)

Climate change and anthropogenic pressure on Bintan Islands, Indonesia: An assessment of the policies proposed by local authorities - Martiwi Diah Setiawati; Muhammad Rizki Nandika; Indarto Happy Supriyadi; Marindah Yulia Iswari; Bayu Prayudha; Sam Wouthuyzen; Novi Susetyo Adi; Yudha Setiawan Djamil; Nuraini Rahma Hanifa; Uday Chatterjee; Aidy M. Muslim; Tsuyoshi Eguchi (Regional Studies in Marine Science, 2023)

Concept design of military and civilian interoperability based on sensing technology to support defense systems in the Malacca Strait region - Mauliza Fatwa Yusdian; Arditho Bramandika Putra; Anatansyah Ayomi Anandari; Debiyanti; La Ode Murgazali Bakasa; Asep Adang Supriyadi; Syachrul Arief; Agus Haryanto (Remote Sensing Applications: Society and Environment, 2023)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)